Charitable acts and lived religion in the funeral sermons of early seventeenth-century women - Emily VINE (E-REA)
This article examines how the lived religious practices of early seventeenth-century English women were presented and memorialised, through an analysis of biographical writing and printed funeral sermons. Focusing on both Catholic and Protestant women who lived and died in London between 1600 and 1660, it suggests that women’s charity work, particularly that which involved active labours such as feeding the poor, tending the sick, and assisting with childbirth, was presented as a key aspect of their lived religion. In this chapter I take ‘lived religion’ to mean practices which individuals, in this case, women, deliberately implemented as a means of having agency over their religious practice. These sources depict charitable acts as being instigated by the individual women themselves, acts which were performed electively, in addition to routines of prayer and contemplation, and acts which were accordingly viewed as an expression of piety and ownership over their religious lives. These descriptions are also moulded to the unique attributes of these individual women; they emphasise the deployment of proficiency in medicine or skill in garment-making, they accentuate the hospitality of these women and occasions where the poor or hungry were invited into the home. These elective charitable works are consequently presented as important forms of ‘active piety’ – as central to and as an important means of acting out one’s faith.